Preventing Surgical Site Infections Using a Natural, Biodegradable, Antibacterial Coating on Surgical Sutures - Jochen Reinbold; Ann-Kristin Uhde; Ingrid Müller; Tobias Weindl; Jürgen Geis-Gerstorfer; Christian Schlensak; Hans-Peter Wendel; Stefanie Krajewski (Molecules, 2017)
Surgical site infections (SSIs) are one of the most common nosocomial infections, which can result in serious complications after surgical interventions. Foreign materials such as implants or surgical sutures are optimal surfaces for the adherence of bacteria and subsequent colonization and biofilm formation. Due to a significant increase in antibiotic-resistant bacterial strains, naturally occurring agents exhibiting antibacterial properties have great potential in prophylactic therapies. The aim of this study was to develop a coating for surgical sutures consisting of the antibacterial substance totarol, a naturally occurring diterpenoid isolated from Podocarpus totara in combination with poly(lactide-co-glycolide acid) (PLGA) as a biodegradable drug delivery system. Hence, non-absorbable monofilament and multifilament sutures were coated with solutions containing different amounts and ratios of totarol and PLGA, resulting in a smooth, crystalline coating. Using an agar diffusion test (ADT), it became evident that the PLGA/totarol-coated sutures inhibited the growth of Staphylococcus aureus over a period of 15 days. A 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay showed that the coated sutures were not cytotoxic to murine fibroblasts. Overall, the data indicates that our innovative, biodegradable suture coating has the potential to reduce the risk of SSIs and postoperative biofilm-formation on suture material without adverse effects on tissue.